Examining the effect of annealing parameters on surface quality and tensile strength of ABS 3D printed materials - Sudin, Mohd Nizam; Shamsudin, Shamsul Anuar; Md Daud, Nazri; Yusuff, Mohd Asri (Tubitak, 2024)
The primary objective of this research is to examine the effects of annealing temperature and duration on the surface quality and tensile strength of ABS-printed materials. ASTM 638 Type IV specimens were created in SolidWorks, sliced using Ultimaker Cura 4.4, and printed with a Creality Ender 3 3D printer using 1.75 mm ABS filament. The samples were subjected to thermal annealing at temperatures ranging from 120◦C to 180◦C. The annealing durations were set at 20, 40, and 60 minutes, after which the samples were cooled down to room temperature. The TR200 roughness tester and Instron 5585 tensile testing machine were utilized to measure surface roughness and tensile strength, respectively. The smoothest surface (0.622µm) was obtained when the temperature was set at 120◦C for a duration of 20 minutes. On the other hand, the roughest surface (3.246µm) was observed when the temperature was increased to 180◦C and maintained for a longer period of 60 minutes. The highest tensile strength of 75.681 MPa was observed at a temperature of 180◦C for a duration of 60 minutes, indicating an optimal condition for maximizing the strength of ABS. However, there may be a limit, as suggested by previous research conducted at temperatures of 160◦C and 180◦C. In conclusion, it can be observed that the relationship between annealing temperature, duration, and surface roughness is not solely linear. The variations observed indicate the presence of interactions between these factors.